Interdisciplinary Geo‐ecological Research across Time Scales in the Northeast German Lowland Observatory (TERENO‐NE). Issue 1 (13th December 2018) - Heinrich, Ingo; Balanzategui, Daniel; Bens, Oliver; Blasch, Gerald; Blume, Theresa; Böttcher, Falk; Borg, Erik; Brademann, Brian; Brauer, Achim; Conrad, Christopher; Dietze, Elisabeth; Dräger, Nadine; et al.
Abstract : Core Ideas: TERENO‐NE investigates the regional impact of global change. We facilitate interdisciplinary geo‐ecological research. Our data sets comprise monitoring data and geoarchives. We are able to bridge time scales from minutes to millennia. The Northeast German Lowland Observatory (TERENO‐NE) was established to investigate the regional impact of climate and land use change. TERENO‐NE focuses on the Northeast German lowlands, for which a high vulnerability has been determined due to increasing temperatures and decreasing amounts of precipitation projected for the coming decades. To facilitate in‐depth evaluations of the effects of climate and land use changes and to separate the effects of natural and anthropogenic drivers in the region, six sites were chosen for comprehensive monitoring. In addition, at selected sites, geoarchives were used to substantially extend the instrumental records back in time. It is this combination of diverse disciplines working across different time scales that makes the observatory TERENO‐NE a unique observation platform. We provide information about the general characteristics of the observatory and its six monitoring sites and present examples of interdisciplinary research activities at some of these sites. We also illustrate how monitoring improves process understanding, how remote sensing techniques are fine‐tuned by the most comprehensive ground‐truthing site DEMMIN, how soil erosion dynamics have evolved, how greenhouse gas monitoring of rewetted peatlands can reveal unexpected mechanisms, and how proxy data provides a long‐term perspective of current ongoing changes.